1958
DOI: 10.1111/j.1467-8306.1958.tb01565.x
|View full text |Cite
|
Sign up to set email alerts
|

MAP SYMBOLS: EQUAL-APPEARING INTERVALS FOR PRINTED SCREENS1

Abstract: common problem in map design is the printing ink. The dot pattern was made as A one of selecting screens with which to dark as possible without having the individual show a scale of values. The screens should, dots coalesce. Figures 1 and 2 show these as closely as possible, give a visual impression screens. commensurate with the values they represent.Some preliminary testing showed that the A typical example would be a rainfall map intervals between the dark tones were too with steps of 10, 20, 40, and 80 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It has been found that perception of gray levels does not change depending on whether the tested gray scale covers the shades between the ultimate margins of black and white, or just its subset, and the curves are very similar for all types of raster patterns and colors with the exception of yellow (R.L. Williams 1958).…”
Section: Brightnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that perception of gray levels does not change depending on whether the tested gray scale covers the shades between the ultimate margins of black and white, or just its subset, and the curves are very similar for all types of raster patterns and colors with the exception of yellow (R.L. Williams 1958).…”
Section: Brightnessmentioning
confidence: 99%
“…Research on the construction of equal value gray scales was conducted by R.L. Williams (1958), A.J. Kimerling (1975) and M.P.…”
Section: Brightnessmentioning
confidence: 99%
“…Eventually though, R.L. Williams (1958) concluded that the curve describing visual perception of value increase is inconsistent with the Fechner's law. As in the case of scaling of the size of graduated symbols, these studies have produced different effects, depending on the experimental method and the structure of the tested areal patterns (raster density).…”
Section: The Psychophysical Stagementioning
confidence: 99%
“…Color and area patterns have also been prominent subjects of research on the human factors of map reading. Studies have been done on the perception of gray-scale intervals (Williams 1958), shading patterns (Jenks and Knos 1961), un-classed cross-hatching (Peterson 1979), and the effect "New perception and cognition studies . .…”
Section: Topics For Research In Cartographic Designmentioning
confidence: 99%